2016
DOI: 10.1080/10934529.2016.1191819
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of organophosphate flame retardants on HepG2, A549 and Caco-2 cells

Abstract: In order to elucidate the cytotoxicity of organophosphate flame retardants (OPFRs), three human in vitro models, namely the HepG2 hepatoma cells, the A549 lung cancer cells and the Caco-2 colon cancer cells, were chosen to investigate the toxicity of triphenyl phosphate (TPP), tributylphosphate (TBP), tris(2-butoxyexthyl) phosphate (TBEP) and tris (2-chloroisopropyl) phosphate (TCPP). Cytotoxicity was assayed in terms of cell viability, DNA damage status, reactive oxygen species (ROS) level and lactate dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 36 publications
(40 reference statements)
2
29
0
Order By: Relevance
“…Specifically, TDCPP caused DNA double-strand breaks and up-regulated expression of γ-H2AX. Results of previous studies have demonstrated that some OPFRs, such as TCEP and, tris (2-chloroisopropyl) phosphate (TCPP) also damage DNA (An et al, 2016). Alternatively, TCPP did not break DNA of V79 cells or in eight strains of the bacterium Salmonella, which indicated the different effect between compounds and cell models used (Föllmann and Wober, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, TDCPP caused DNA double-strand breaks and up-regulated expression of γ-H2AX. Results of previous studies have demonstrated that some OPFRs, such as TCEP and, tris (2-chloroisopropyl) phosphate (TCPP) also damage DNA (An et al, 2016). Alternatively, TCPP did not break DNA of V79 cells or in eight strains of the bacterium Salmonella, which indicated the different effect between compounds and cell models used (Föllmann and Wober, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, TCPP did not break DNA of V79 cells or in eight strains of the bacterium Salmonella, which indicated the different effect between compounds and cell models used (Föllmann and Wober, 2006). ROS can function as "redox messengers" in intracellular signaling (Yang et al, 2014) and inducers of oxidative damage, which are related to various biological processes, such as DNA damage, viability, proliferation and death of cells (An et al, 2016). Our results showed that the RAW264.7 cells began to produce ROS when the exposure time reached 6 hr, the increasing rate peaked at 12 hr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Our previous study also showed that TBP and TBEP exposure (24 h) below 100 μM seems to have no remarkable proliferation-inhibiting effect on HepG2, human lung cancer (A549) and human colon cancer (Caco-2) cells. 40 Reactive oxygen species (ROS) are well-established inducers of oxidative damage, which is closely related to cell viability, proliferation and cell death. 41 ROS formation might be a pivotal mechanism behind the toxicity of multiple environmental chemical toxins, such as polychlorinated biphenyls (PCBs), PBDEs, organic phosphorus pesticides, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other organophosphate FRs tested within the same cell line, TCEP had some of the lowest levels of cytotoxicity measured. For instance, tributylphosphate, tris(2‐butoxyethyl) phosphate and tris(1‐chloro‐2‐propyl)phosphate showed significant effects on HepG2 cell viability at 200 μ m after 24 hours treatment (An et al, ), while tris(1,3‐dichloro‐2‐propyl) phosphate, a structural analogue of TCIPP, had an IC 50 of 84.0 μ m after 72 hours of exposure (Zhang, Williams, et al, 2016). However, it should be noted that perhaps TCIPP cytotoxic effects only occur at doses higher than 100 μ m , the maximum dose used in this study, as evidenced by cytotoxic effects only being seen at 200 μ m in the same cell line that was used in this study (An et al, ).…”
Section: Discussionmentioning
confidence: 99%